WORKSHOP PENGEMBANGAN INSTRUMEN EVALUASI PEMBELAJARAN DI SEKOLAH DASAR - Avana, Nurlev (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2024)
Evaluation tools must reflect the learning objectives in the curriculum so that evaluation results provide an accurate picture of student achievement. This workshop aims to provide training in developing learning evaluation instruments in elementary schools. Learning instruments are currently very much needed by students because, with these learning instruments, they can measure the level of students' liking for subjects. The instrument that will be developed contains questions of factual knowledge based on a grid of essential competencies, assessment indicators, and cognitive domains, the learning themes for class IV students. Teachers and prospective teachers are in the training for developing learning instruments in elementary schools. PKM activities are carried out synchronously (virtually) or asynchronously at different places and times using a service learning approach. The service results show that the material meets the needs of elementary school teachers to improve their professionalism, especially in making learning instruments.